A quality-oriented urban development pattern? Two case studies in Shanghai - Xin Yi (Journal of Urban Management, 2014)
This article concentrates on the transformation of development patterns due to economic transitions in Shanghai through two case studies looking at different spatial levels. In the transformation process, the improvement of spatial quality in the existing urban space will play the central role in achieving a balance in the future among the relevant economic, social and environmental aspects. Relatedly, economic growth is no longer seen as the only important goal. Social and environmental issues have gained more and more attention, and are increasingly seen as the basic foundation for sustainable development. Given that such significant changes have occurred within a very short period of time, the author will discuss different critical factors and related symptoms as embodied in urban planning practice. Two case studies regarding the transformation in goal setting and the implementation process will be introduced, with a focus on the issues of accessibility and quality of life. One case relates to the development plan for Hongqiao Business Park, which is one of three focus development areas for Shanghai and is located near the comprehensive Hongqiao Transport Hub. The other case considers an area located to the south of the area of interest in the first case; both areas are well connected with each other. A new development strategy for the development of new towns in knowledge economy clusters has been advanced in the outskirts of Shanghai's city center, and has also influenced such efforts on the regional level, i.e., where the Huangpu River flows through the planning area and connects to other parts of the broader Shanghai region.
Keywords: 710; economic transition; Quality-oriented; Shanghai; urban development pattern